Ecologia e comportamento do bicudinho-do-brejo (Stymphalornis acutirostris Bornschein, Reinert & Teixeira, 1995 - aves, Thamnophilidae) - Reinert, Bianca Luiza [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Stymphalornis acutirostris (bicudinho-do-brejo) (9,8 g), insetívoro, descrito em 1995, é o único Thamnophilidae palustre. Ameaçado de extinção, distribui-se em oito populações isoladas do litoral do Paraná ao do norte de Santa Catarina, que totalizam 6.060 ha de área de ocupação. Foram realizadas c. 2.000 h de observações gerais de 2006 ao início de 2008 na ilha do Jundiaquara (11,6 ha) e entorno, baía de Guaratuba, Paraná, onde todos os indivíduos foram marcados. A coloração da plumagem juvenil é distinta da dos adultos e revela dimorfismo sexual. Com sete meses de idade, machos adquirem plumagem similar à dos adultos, fato pouco conhecido na família. A espécie defende território ao longo do ano e é monogâmica. Divórcios, entretanto, foram registrados e uma fêmea esteve pareada com dois machos ao mesmo tempo. A ilha comportou 15 territórios em um ano e 14 no outro, os quais mediram 0,67 ha, em média, e permaneceram estáveis. Nova estimativa populacional é apresentada (12.942 indivíduos). Vegetação herbácea mais alta e densa foi selecionada para a nidificação. Alguns ninhos foram alagados pela maré e alguns ovos que ficaram submersos eclodiram. Um macho com 12 anos reproduziu e outro, com sete meses, esteve pareado e defendendo território. Os casais realizaram de uma a oito tentativas de nidificação em uma estação reprodutiva. O casal se incumbe do cuidado parental diurno. O macho visitou mais regularmente o ninho durante a construção e incubação (n.s.); a fêmea visitou o ninho com mais regularidade durante a alimentação (n.s.) e permaneceu mais tempo junto a ele durante a construção (p = 0,006) e incubação (n.s.). O sucesso reprodutivo, a partir da incubação, foi de 15,41% pela taxa simples e 23,91% pelo método de Mayfield. Na construção do ninho, a maior causa de insucesso foi o abandono (77,6%); na incubação...

Stymphalornis acutirostris (Marsh Antwren) (9. 8 g) is an insectivorous bird described in 1995, being the only Thamnophilidae restricted to marsh habitats. Threatened of extinction, it’s distributed in eight isolated populations in Paraná and northern Santa Catarina coasts, totaling an occupation area of 6,060 ha. Two thousand hours of observations were carried out from the beginning of 2006 till the same period in 2008 at the Jundiaquara Island (11. 6 ha) and its surroundings in Guaratuba bay, Paraná, where all the individuals were banded. Juvenile plumage is distinct from that of the adults and it shows sexual dimorphism. Sevenmonths- old males acquire plumage similar to adults, an exceptionally premature acquisition in the family. The species is monogamous and holds a year-long territory. However, divorces were registered, and one female was paired with two males at the same time. The Island held 15 stable territories in one year, 14 of which remained the next year, with mean territory size of 0.67 ha. A new population estimation is presented (12,942 individuals). Taller and denser herbaceous vegetation were selected for nesting. Some nests were reached by the tides and some submerged eggs hatched. A 12 years old male was reproducing and another, seven months old, was paired and defending his territory. The couples did from one to eight nesting attempts in a single reproductive season. Both parents are charged with parental care. Males visited the nest more frequently during its construction and incubation period (n.s.), while females visited more during the nestling feeding period (n.s.), and stayed more time near it during construction (significant differences) and incubation (n.s.). The mean reproductive success, from incubation, was 15.41% using absolute numbers, and 23.91% by the Mayfield method. During nest construction, the main cause of losses was abandon (77.6%), during... (Complete abstract click electronic access below)
Keywords: Ave; Ecologia; Ave - Comportamento; Bicudinho-do-brejo; Birds